PENERAPAN METODE ROTOSCOPING DAN FRAME ELIMINATION PADA ANIMASI 2D TARI ZAPIN - Rokhmatulloh Batik Firmansyah; Dhimas Adi Saputra; Chyntia Dianly Lukman; Qashdan Aqil Al-Bajili; Jimmy Cristian (LPPM Universitas Abdurrab, 2024)
The growth of the animation industry in Indonesia is predicted to continue to grow. This can be seen from the development of animation in Indonesia, which is dominated by 2-dimensional and 3-dimensional animation in recent years, as well as being marked by the large number of animators from Indonesia who are successful on the international stage. Generally, animation is applied to character movements, whether simple movements such as walking, to complex movements such as fighting. In its application, various methods can be used as long as they can create animated movements that match the original movements. Generally this is done successfully because in complex movements, the speed of the movement seems to obscure the animation details of the movement. However, this does not apply to one type of movement that is very rarely used in animation, this movement is dancing. The reason why dance movements are rarely animated is because dance is a series of movements that have low speed, so that the details in each change in movement in one dance can produce hundreds or even thousands of frames when converted into animation. Visualizing dance art with animated visuals is not an easy thing, because there are many frames that have to be created so that the dance looks natural. Moreover, using animation techniques such as frame by frame and cutout, of course, actually increases the processing time and quantity of images produced. Actually, apart from frame by frame and cutout, there are still other animation techniques that can be applied to overcome the problem of many frames in dance movements. One solution is to visualize dance in animated form. Namely the rotoscoping technique which can bridge dance with animation. This rotoscoping imitates every change in movement in dance, and converts it into a frame. However, if you only use this technique, the resulting image will still be too large, so one more technique needs to be added, namely frame elimination. For this reason, the author wants to apply the rotoscoping technique in making Zapin dance animations. To find out whether dance art can be visualized well using rotoscoping and Frame Elimination techniques.